LEARN MORE ABOUT BUCKY- BALL - Sharma, S.V. (SCHOOL SCIENCE, 2012)
Carbon has been known as the king of elements because of its versatility and diversity in all areas. Currently, it has three allotropic forms viz., diamond, graphite and buckminsterfullerene (C60)or bucky-ball, in short. Diamond has been prized for centuries as a gemstone of extraordinary beauty, brilliance and lustre. The word diamond derives its name from the alteration of the Latin word adamas meaning ‘untamable’ referring to its hardness. The name graphite comes from the greek verb graphian meaning ‘to write’. It has been used in lubricants, seals, insulators, filters, refractors, electrodes and writing material. Bucky-ball, the third form of carbon, was synthesised in laboratory by Smalley and Kroto (1985). Scientists have been speculating that bucky-ball might be formed every time we light a candle.